Integrating values of ecosystem services into decision making in coastal management in Xiamen. (15th June 2021) - Su, Meina; Peng, Benrong
Abstract: This study presents three case studies of integrating coastal ecosystem services' value into decision making in Xiamen under the integrated coastal management (ICM) framework. Xiamen's experiences show that integrating the values of ecosystem services into decision making can harmonize coastal economic development, environmental protection, and local stakeholders' concerns regarding preserving the ecosystems they depend on. Scientists play a critical role in integrating the values of ecosystem services into decision making by convincing policymakers and concerned stakeholders that the benefits and costs of development and conservation of ecosystems are worthwhile. ICM also provides the required operational framework and policy mechanism for incorporating ecosystem services and their values into decision making, especially at times of market and institutional failures. Highlights: Local stakeholders have the greatest incentive to preserve the ecosystems they depend on when they understand the VES. Integrating the VES into decision making could harmonize and sustain socioeconomic development and environmental protection. Interdisciplinary experts play a very important role in integrating VES into decision making. ICM provides the needed operational framework and policy mechanism for integrating VES into decision-making.